Approaches to Speech Therapy for Children with Autism Spectrum Disorders (ASD) - Нryntsiv, Mariana; Zamishchak, Mariia; Bondarenko, Yuliia; Suprun, Hanna; Dushka, Alla (International Journal of Child Health and Nutrition, 2025)
Background: The article analyzes methods of correcting speech disorders in children with autism spectrum disorders (ASD). It is based on a literature review and practical cases on this issue. Methods: The study used observation methods of behavior, speech, and communication of children with ASD, questionnaires from parents, educators, and correctional teachers, and experimental research based on the information obtained. The main methods of correction of speech disorders in children with ASD are highlighted, which include speech therapy, alternative and augmentative communication (AAC), therapy using games and imitation techniques, the use of behavioral techniques, and multisensory approaches. Traditional and innovative means for implementing the outlined methods of correction of speech disorders in children with autism spectrum disorders are outlined. A methodology for determining the effectiveness of the use of methods for the correction of speech disorders in children with autism spectrum disorders is proposed. Results: Criteria and indicators for evaluating the outlined methods of correcting speech disorders have been developed. The main criteria include speech development, development of communication and social skills, reduction of stereotypical and repetitive forms of speech, emotional and behavioral regulation, use of alternative means of communication, and individual progress. Based on the developed criteria, a survey was conducted among parents, educators, and therapy specialists on the effectiveness of using the outlined methods of correcting speech disorders. The effectiveness of the use of traditional and innovative means of correction of speech disorders in the context of the implementation of the outlined methods of speech correction in children with ASD was experimentally tested. The effectiveness of the above methods was tested for different groups of children with ASD, including preschool, school, and adolescent age. In the course of the test, the control group used traditional means, and the experimental group used a combination of traditional and innovative means of correcting speech disorders in children with autism spectrum disorders (ASD). Conclusion: The positive influence of the combination of traditional and innovative means of correction of speech disorders in children with autism spectrum disorders (ASD) on the development of language skills is noted.